PENILAIANKINERJA KOPERASI PEGAWAI REPUBLIK INDONESIA (KPRI) â€SRI REJEKIâ€ KECAMATAN DONOMULYO BERDASARKAN PERATURAN MENTERI NEGARA KOPERASI DAN USAHA KECIL DAN MENENGAH NO.14/PER/M.UMKM/XII/2009 - Wiseptya, Agris; Indrawati, Nur Khusniyah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
The existence of cooperative useful as a pillar of the national economy, according lofty goals listed in Pancasila and the 1945 Constitution is to realize prosperity for all Indonesian people.This study aims to analyze the health of financial and non-financial in Employees Cooperative Republic of Indonesia